Effects of genotype and growing substrate on bio-efficiency of gourmet and medicinal mushroom, Lentinula edodes (Berk.) Pegler (Bangladesh Journal of Botany, 2019)
The preference of a particular strain to a specific substrate in shiitake mushroom was investigated. The effect of different genotypes (DMRO-34, DMRO-23, DMRO-327 and DMRO-388s), substrates (sawdust and wheat straw) and their interactions were found highly significant for yield and yield attributing factors. Strain DMRO-388s recorded the highest bio-efficiency (85.63%) on saw dust (SD) and the strain DMRO-327 with 53.02% on wheat straw (WS). The mycelial colonization was rapid on SD, while the sporophore formation was found earlier on WS. Breakdown of phenolic compounds in the substrate was found much higher in WS particularly with strain DMRO-327. Ability of the strains to degrade lignin content was found higher by the strain DMRO-388s (58.78%) in SD. Hemicellulose concentration decreased in both the substrates with each passing growth stage and it was found much rapid with DMRO-388s after spawn run stage. Of the substrates used, SD gave higher yield over the WS. But the earliness of fruiting on WS can economize the cost of shiitake cultivation as it is cheap and abundantly available.